Methane-Dependent Extracellular Electron Transfer at the Bioanode by the Anaerobic Archaeal Methanotroph “Candidatus Methanoperedens” - Ouboter, Heleen T.; Berben, Tom; Berger, Stefanie; Jetten, Mike S. M.; Sleutels, Tom; Ter Heijne, Annemiek; Welte, Cornelia U. (Frontiers in Microbiology, 2022)
Anaerobic methanotrophic (ANME) archaea have recently been reported to be capable of using insoluble extracellular electron acceptors via extracellular electron transfer. In this study, we investigated extracellular electron transport by a microbial community dominated by ‘Candidatus Methanoperedens’ archaea at the anode of a bioelectrochemical system poised at 0 V vs standard hydrogen electrode, in this way measuring current as a direct proxy of extracellular electron transport by this community. After inoculation of the bioelectrochemical system, the maximum current density was 274 mA m-2 (stable current up to 39 mA m-2). Concomitant conversion of 13CH4 into 13CO2 demonstrated that current production was methane-dependent, with 38% of the current attributed directly to methane supply. Based on current production and methane uptake in a closed system, the coulombic efficiency was about 17%. Polarization curves demonstrated that the current was limited by microbial activity at potentials above 0 V. The metatranscriptome of the inoculum was mined for expression of c-type cytochromes potentially used for extracellular electron transfer, leading to the identification of several multiheme c-type cytochrome-encoding genes among the most abundant transcripts in ‘Ca. Methanoperedens’. Our study provides strong indications of extracellular electron transfer in ANME archaea and describes a system in which ANME-mediated extracellular electron transport can be investigated under laboratory conditions, providing new research opportunities for mechanistic studies and possibly the generation of axenic ANME cultures.